Estimation of temporal evolution of the helium plasmasphere based on a sequence of IMAGE/EUV images. Issue 5 (15th May 2014) - Nakano, S.; Fok, M.‐C.; Brandt, P. C.; Higuchi, T.
Abstract We have developed a technique for estimating the temporal evolution of the plasmaspheric helium ion density based on a sequence of extreme ultraviolet (EUV) data obtained from the IMAGE satellite. In the proposed technique, the estimation is obtained by incorporating EUV images from IMAGE into a two‐dimensional fluid model of the plasmasphere using a data assimilation approach based on the ensemble transform Kalman filter. Since the motion and the spatial structure of the helium plasmasphere is strongly controlled by the electric field in the inner magnetosphere, the electric field around the plasmapause can also be estimated using the ensemble transform Kalman filter. We performed an experiment using synthetic images that were generated from the same numerical model under a certain condition. It was confirmed that the condition that generated the synthetic images was successfully reproduced. We also present some results obtained using real EUV imaging data. Finally, we discuss the possibility of estimating the density profile along a magnetic field line. Since each EUV image was taken from a different direction due to the motion of the IMAGE satellite, we could obtain the information on the density profile along a field line by combining multiple images.